Antifungal Activity the Active Fraction of Orange Jasmine (Murraya paniculata (Linn) Jack) Leaves and Stem Bark Against Malassezia furfur: Aktivitas Antifungi Fraksi Aktif Daun dan Kulit Batang Kemuning (Murraya paniculata (Linn) Jack) terhadap Malassezia furfur - Mulangsri, Dewi Andini Kunti; Rosella, Sevitia; Isna Azmut Baroroh (Universitas Tidar, 2024)
Leaves and stem bark of orange jasmine have bioactive compounds such as phenol and flavonoids, which these compounds could be extracted by organic solvent and have antifungal activity against Malassezia furfur which cause excema, dandruff and tinea versicolor in humans. Fractionation of the extract would obtain a specific compound based on the polarity of the solvent. This research aims to know the active fraction of leaves and stem bark of orange jasmine which had antifungal activity against Malassezia furfur. The simplicia powder of leaves and stem bark orange jasmine was macerated with 96% ethanol solvent and then fractionated as gradually with n-hexane, ethyl acetate, and water solvent. The antifungal activity of ethanol extract and fractions was tested against Malassezia furfur with 80; 90; 100% concentration by disk diffusion method at 37˚C for 48 hours of incubation. The data of antifungal activity was analyzed by two-way ANOVA. The result of this research showed antifungal activity from active fraction as water fraction of leaves and stem bark of orange jasmine against Malassezia furfur. The diameter of inhibition zones for the active fraction of leaves and stem bark of orange jasmine such as 8.6 – 14 mm and 12.3 – 15.8 mm respectively.